Business Process Analysis And Odoo Implementation For Retail Industry - Siregar, Ivan Michael; Fiestyawan, Christian; Sirait, Tamsir Hasudungan (STMIK Banjarbaru, 2025)
Distribution companies face significant challenges due to reliance on manual processes in sales recording, inventory management, and order processing, leading to operational inefficiencies and financial losses. This study aimed to implement an integrated Enterprise Resource Planning system that automates order processing and real-time inventory monitoring. The methodology included business process analysis, system design, implementation, and system evaluation. The case study was conducted at SSN, a company engaged in the distribution of retail commercial products. The results showed that the implemented system reduced order processing time from 15–40 minutes to 5–10 minutes, increasing efficiency by 75%. The error rate in order entry decreased from 12% to 3%, while inventory discrepancies dropped from 41% to 10%. This implementation has been proven to improve operational efficiency, data accuracy, and optimize inventory management in the distribution industry. Keywords: Odoo; ERP; Sales; Inventory; Inventory management; Manual proccess. AbstrakPerusahaan distribusi menghadapi tantangan signifikan akibat ketergantungan pada proses manual dalam pencatatan penjualan, pengelolaan inventaris, dan pemrosesan pesanan, yang menyebabkan inefisiensi operasional dan kerugian finansial. Penelitian ini bertujuan untuk mengimplementasikan sistem Enterprise Resource Planning terintegrasi yang mengotomatisasi pemrosesan pesanan dan pemantauan inventaris secara real-time. Metodologi yang digunakan meliputi analisis proses bisnis, perancangan sistem, serta implementasi dan evaluasi sistem. Studi kasus dilaksanakan pada perusahaan SSN yang bergerak dalam bidang distribusi produk komersil. Hasil penelitian menunjukkan bahwa sistem yang diterapkan mampu mengurangi waktu pemrosesan pesanan dari 15-40 menit menjadi 5-10 menit, meningkatkan efisiensi sebesar 72%. Tingkat kesalahan dalam entri pesanan berkurang dari 12% menjadi 3%, sedangkan ketidaksesuaian inventaris turun dari 41% menjadi 10%. Implementasi ini terbukti meningkatkan efisiensi operasional, akurasi data, serta mengoptimalkan pengelolaan inventaris dalam industri distribusi.